2000
DOI: 10.1007/bf02674530
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporters and glucose utilization in rat brain after acute ethanol administration

Abstract: In the normal adult brain, glucose provides 90% of the energy requirements as well as substrate for nucleic acid and lipid synthesis. In the present study, effects of ethanol on glucose transporters (GLUT) and glucose utilization were examined in rat brain. Male Sprague-Dawley rats weighing 250-300 gms were given either ethanol 3 gm/kg BW or saline i.p. 4 hrs prior to the animal sacrifice and removal of the cerebral cortical tissue. The cortical plasma membranes analyzed by cytochalasin B binding assay showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…In addition to regulating glucose utilization, insulin can stimulate glucose uptake. Glucose uptake is mediated by glucose transporter molecules termed GLUTs [73], and previous studies demonstrated that chronic gestational exposure to ethanol inhibits expression and function of GLUT molecules in the brain [74][75][76]. Correspondingly, the present work demonstrated significantly reduced levels of GLUT2 and GLUT4 gene expression, as well as reduced levels of ATP in cerebellar tissue from ethanol-exposed pups.…”
Section: Effects Of Ethanol On Insulin and Igf-i Rtk Activitiessupporting
confidence: 67%
“…In addition to regulating glucose utilization, insulin can stimulate glucose uptake. Glucose uptake is mediated by glucose transporter molecules termed GLUTs [73], and previous studies demonstrated that chronic gestational exposure to ethanol inhibits expression and function of GLUT molecules in the brain [74][75][76]. Correspondingly, the present work demonstrated significantly reduced levels of GLUT2 and GLUT4 gene expression, as well as reduced levels of ATP in cerebellar tissue from ethanol-exposed pups.…”
Section: Effects Of Ethanol On Insulin and Igf-i Rtk Activitiessupporting
confidence: 67%
“…In sheep and humans, fetal glucose is almost entirely acquired from the mother via the placenta (2,18) and one would expect that decreases in maternal blood glucose would be reflected by a similar decrease in fetal blood glucose. The lack of substantial hypoxemia in the fetus following EtOH exposure could be a result of decreased fetal glucose utilization; EtOH is known to inhibit fetal glucose transporters GLUT1 and GLUT3 (15,34). Decreased fetal glucose uptake and utilization could explain the observed trend toward a reduction in ponderal index in our EtOH-treated fetuses.…”
Section: Fetal Blood Glucose Concentrationsmentioning
confidence: 53%
“…Ethanol may also impair fetal tissue uptake of nutrients from the fetal circulation, for example by decreasing the expression and activity of glucose transporters. Ethanol administration to adult rats rapidly decreases plasma membrane abundance of GLUT1 and GLUT3 in the cerebral cortex (19), and GLUT1 expression and in vivo and in vitro glucose uptake are reduced in brain tissue of ethanol-exposed fetal rats (37,38). These studies suggest that both impaired placental transport of nutrients and impaired fetal tissue uptake of nutrients may contribute to fetal growth restriction caused by acute ethanol exposure.…”
Section: Discussionmentioning
confidence: 78%